2002
DOI: 10.1042/bst0300351
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of 14-3-3 isoform dimer interactions and phosphorylation

Abstract: Proteins that interact with 14-3-3 isoforms are involved in regulation of the cell cycle, intracellular trafficking/targeting, signal transduction, cytoskeletal structure and transcription. Recent novel roles for 14-3-3 isoforms include nuclear trafficking the direct interaction with cruciform DNA and with a number of receptors, small G-proteins and their regulators. Recent findings also show that the mechanism of interaction is also more complex than the initial finding of the novel phosphoserine/threonine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 2 publications
4
116
1
1
Order By: Relevance
“…Several lines of evidence support this concept. 14-3-3 isoforms function as homo-and heterodimers that link their binding partners (Yaffe et al, 1997;Aitken et al, 2002). 14-3-3 isoforms (sigma and zeta) bind to APC (Jin et al, 2004;Meek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence support this concept. 14-3-3 isoforms function as homo-and heterodimers that link their binding partners (Yaffe et al, 1997;Aitken et al, 2002). 14-3-3 isoforms (sigma and zeta) bind to APC (Jin et al, 2004;Meek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 14-3-3 linking α3*nAChRs to APC would tether the receptors to the postsynaptic cytoskeleton and provide an additional mechanism by which 14-3-3 interactions promote the stable retention of α3*nAChRs at postsynaptic sites. Because 14-3-3 binding to its target proteins is often phosphorylation-dependent (Muslin et al, 1996;Aitken et al, 2002), the decreases in 14-3-3 synaptic accumulation in APC::EB1-dn expressing neurons may reflect changes in signaling events at the synapse. The reduced levels of functional α3*nAChRs may cause decreases in activity-dependent downstream signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that c-Abl is tethered in the cytoplasm by binding to 14-3-3 proteins and that the c-Abl-14-3-3 complexes are disrupted after genotoxic stress or oxidative stress. Functional binding analyses demonstrated that this binding depends on phosphorylation of c-Abl at Thr735, which is included within the 14-3-3 binding motif RSXpS/TXP (Aitken et al, 2002). Importantly, Thr735 is located between the second and third nuclear localization signals in the C terminus of c-Abl, suggesting that binding of 14-3-3 to phosphorylated Thr735 masks the c-Abl nuclear localization signals and prevents its nuclear entry.…”
Section: Introductionmentioning
confidence: 99%
“…Two canonical 14-3-3-binding motifs have been identified as R(S/X)XpSXP and RXXXpSXP, where pS repre-sents phospho-serine or phospho-threonine and X any amino-acid [12]. Association with 14-3-3 proteins regulates the function of ligands by inter-and intra-compartmental sequestration, activation/inactivation of enzymatic activity and promotion/inhibition of protein-interactions; thereby, numerous cellular processes in all multi-cellular species analyzed are regulated by 14-3-3 proteins (reviewed in [1,13,14]). In part this regulation is mediated by conformational changes of the ligand after association with 14-3-3 proteins [15].…”
Section: Introductionmentioning
confidence: 99%